Wrestling with nature : from omens to science - Harrison, Peter, 1955-; Numbers, Ronald L.; Shank, Michael H. (University of Chicago Press, 2011)
When and where did science begin? Historians have offered different answers to these questions, some pointing to Babylonian observational astronomy, some to the speculations of natural philosophers of ancient Greece. Others have opted for early modern Europe, which saw the triumph of Copernicanism and the birth of experimental science, while yet another view is that the appearance of science was postponed until the nineteenth century. Rather than posit a modern definition of science and search for evidence of it in the past, the contributors to Wrestling with Nature examine how students of nat.